Access Ligation in Transplant Patients. Issue 1 (March 2016) - Wilmink, Teun; Hollingworth, Lee; Dasgupta, Indranil
Access surgeons will encounter patients with functioning transplants who want to lose their fistula, and every dialysis unit sees patients returning after a failed kidney transplant for whom an old fistula is a readily available lifeline. The decision is straightforward in patients with perfectly functioning transplants and disabling complications of their fistula, or in patients with failing transplants and a good fistula. The challenge is to make this decision in patients with good transplant function and an asymptomatic fistula. Despite improvements in one-year survival of renal grafts, the long-term graft survival has improved modestly. This means about half of the patients with a successful kidney transplant will return to dialysis within 10 years. Use of recently developed risk calculators, based on clinical parameters, may help in the decision process. A high flow fistula can lead to heart failure but most fistulae are well tolerated in asymptomatic patients and the effects of closure of the AVF on the heart are modest. Recent evidence suggests that there may be benefits of a functioning AVF that may need to be considered in this decision process. This article reviews the literature and comes to pragmatic recommendations of what to do with this conundrum.